Explainable Artificial Intelligence (XAI) Models for Transparent and Accountable Fraud Detection in Banking Ecosystems (International Journal of Scientific Research and Management (IJSRM), 2025)
Digital fraudulent activities are reminiscent of the technological sophistication of the contemporary age. Every financial institution, therefore, needs to adopt innovation in the use of fraud detection systems, hence the introduction of Artificial Intelligence (AI), which sits squarely in this technological age. Despite the consecutive developments of high-performing AI systems, including Deep Learning and High-Performing Ensemble Classifiers, why, then, is it still hard to accept such systems in banking and finance? This stems from the fact that most of them remain ‘black boxes’, i.e, invalidating themselves as any means of implementation since they cannot be ‘verified’. This paper discusses the introduction of Explainable Artificial Intelligence (XAI) into fraud detection networks, utilizing advanced fraud prevention instrumentation such as fraud detection technologies, along with its potential benefits and challenges. By using realistic datasets such as the ’Fraud Detection in Banking Ecosystems’, ‘Resource Usage Partitioning(D) Technologies’ datasets, and ‘Identity Theft Protection Scams’ datasets, we review some of the top most XAI methods available each of which includes SHapley Additive exPlanations (SHAP), Local Interpretable Model-Agnostic Explanations (LIME), Partial Dependence Plots (PDP) and counterfactual reasoning. By incorporating XAI layers into a new hybrid ensemble that combines CatBoost, XGBoost, and LightGBM, the proposed approach advocates for and analyzes boosting frameworks. Such models, it has been found, achieve better than 99 percent performance in fraud detection while still providing healthy explanations for each of their predictions. Additionally, this research captures the recent international governance structures in the area of algorithmic recommendations. These structures include, but are not limited to, the EU regulation on Artificial Intelligence (AI), the U.S. oversight mechanisms of algorithms, and the ‘Right to Explanation (GDPR)’ among others, in conjunction with the importance of XAI in cross-border operations. The results reveal a clear pattern of implementation for fraud detection growth theories, where explainable systems are integrated throughout the banking system without compromising efficiency.